Experience of Preimplantation Genetic Diagnosis with HLA Matching at the University Hospital Virgen del Rocío in Spain: Technical and Clinical Overview. (24th April 2014) - Fernández, Raquel María; Peciña, Ana; Lozano-Arana, Maria Dolores; Sánchez, Beatriz; Guardiola, Jordi; García-Lozano, Juan Carlos; Borrego, Salud; Antiñolo, Guillermo
Abstract : Preimplantation genetic diagnosis (PGD) of genetic diseases, combined with HLA matching (PGD-HLA), is an option for couples at risk of transmitting a genetic disease to select unaffected embryos of an HLA tissue type compatible with that of an existing affected child. Here we present the results of our PGD-HLA program at the Department of Genetics, Reproduction and Fetal Medicine of the University Hospital Virgen del Rocío in Seville. Seven couples have participated in our program because of different indications. Overall, 26 cycles were performed, providing a total of 202 embryos. A conclusive molecular diagnosis and HLA-typing could be assured in 96% of the embryos. The percentage of transfers per cycle was 26.9% and the birth rate per cycle was 7.7% per transfer. Our PGD-HLA program resulted in the birth of 2 healthy babies, HLA-identical to their affected siblings, with successful subsequent haematopoietic stem cell (HSC) transplantations. Both HSC-transplanted children are currently doing well 48 and 21 months following transplantation, respectively. All the procedures, including HSCs umbilical cord transplantation, were performed in our hospital.